1983
DOI: 10.1530/jrf.0.0690671
|View full text |Cite
|
Sign up to set email alerts
|

Luteal function after ovulation blockade by intrafollicular injection of indomethacin in the ewe

Abstract: The dominant follicle of oestrous ewes was injected with saline or indomethacin. Treated follicles were obtained at 2 and 10 days after treatment and examined histologically. Indomethacin-injected follicles were abnormally enlarged and remained unruptured. On Day 2 after treatment, these follicles appeared grossly hyperaemic. The follicular walls of control and indomethacin-treated groups had luteinized. Blood samples for the measurement of serum progesterone were collected from animals with their ovaries left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…(Ginther, 1974), also failed to block ovulation in any of the cows treated. (1979) and Murdoch & Dunn (1983) also noted luteinization of the follicles that had not undergone ovulation after indomethacin treatment. Two previous studies (Shemesh & Hansel, 1975;Shemesh, 1979) showed that bovine follicular tissue synthesized PGs under in-vitro conditions and that synthesis was enhanced by LH.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…(Ginther, 1974), also failed to block ovulation in any of the cows treated. (1979) and Murdoch & Dunn (1983) also noted luteinization of the follicles that had not undergone ovulation after indomethacin treatment. Two previous studies (Shemesh & Hansel, 1975;Shemesh, 1979) showed that bovine follicular tissue synthesized PGs under in-vitro conditions and that synthesis was enhanced by LH.…”
Section: Resultsmentioning
confidence: 88%
“…The ovulatory failure may be confined to the preovulatory follicle because after the LH surge, prostaglandin (PG) synthesis within the preovulatory follicle is critically involved in ovulation (Espey, 1980; Armstrong, 1981) and if PG synthesis does not occur then the preovulatory follicle would not rupture and possibly remain as a cyst. Ovulation has been successfully blocked by indomethacin, an inhibitor of PG synthesis, in the mouse (Lau, Saksena & Chang, 1974), rat , rabbit (Grinwich, Kennedy & Armstrong, 1972), monkey (Wallach, de la Cruz, Hunt, Wright & Stevens, 1975), sow (Ainsworth et al, 1979) and ewe (Murdoch & Dunn, 1983) (Steel & Torrie, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that inhibition of follicle rupture by injection of PGE 2 synthesis inhibitor or indomethacin into preovulatory follicle just before LH surge does not alter luteal function in the following luteal phase of cattle [14], sheep [15], and monkeys [16]. In addition, injection of LH into sheep and rabbit preovulatory follicles induced luteinization and P 4 secretion without ovulation [17].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of indomethacin (PG synthetase inhibitor) to block ovulation is documented for rats (Tsafriri et al, 1973), rabbits (O'Grady et al, 1972), sheep (Murdoch & Dunn, 1983) and cattle (De Silva & Reeves, 1985). Intrafollicular injection of PGF-2a antiserum blocked luteinizing hormone (LH)-induced ovulations in rabbits (Armstrong et al, 1974).…”
Section: Discussionmentioning
confidence: 99%